Dinamika Iklim Berdasarkan Rekam Data Sporomorf pada Sedimen Sungai Bengawan Kabupaten Cilacap - Setijadi, Rahmat; Suedy, Sri Widodo Agung (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Sporomorphs data that recorded in the sediments can be used as an indicator in predicting of the dynamics climate during Holocene. By knowing the type of pollen and spores, so it willÂ known the plant species that producing palynomorphs. By knowing sporomorphs fossils species that were found widely in sedimentary rocks is a right way to explore the climate change that occurred in the past. The purposes of this research is to develop a bio-prediction method using sporomorph fossils to determine changes in sea level caused by climate change. The research included field-works and laboratory studies . Field research for rock sampling and laboratory studies for sediments preparations include making microscopic slide, identification and classification of fossil, and palynology data analysis. The study found 46 type sporomorphs, that consistsÂ 16 types of arboreal pollen, 6 types of non-arboreal pollen and 24 types Pteridophyta. Four climate change events have been occurred: the Dry climate of first period; Second period turned into a wet climate; the third period became dry climate; Â and the fourth period that the climate were become wetter. Keywords: arboreal pollen, non arboreal pollen, sporomorphs, climate